In your face: transcendence in embodied interaction - Gallagher, Shaun (Frontiers in Human Neuroscience, 2014)
In cognitive psychology, studies concerning the face tend to focus on questions about face recognition, theory of mind and empathy. Questions about the face, however, also fit into a very different set of issues that are central to ethics. Based especially on the work of Levinas, philosophers have come to see that reference to the face of another person can anchor conceptions of moral responsibility and ethical demand. Levinas points to a certain irreducibility and transcendence implicit in the face of the other. In this paper I argue that the notion of transcendence involved in this kind of analysis can be given a naturalistic interpretation by drawing on recent interactive approaches to social cognition found in developmental psychology, phenomenology, and the study of autism.